Evaluation of the ACR and SLICC classification criteria in juvenile-onset systemic lupus erythematosus: a longitudinal analysis. (October 2017) - Lythgoe, H; Morgan, T; Heaf, E; Lloyd, O; Al-Abadi, E; Armon, K; Bailey, K; Davidson, J; Friswell, M; Gardner-Medwin, J; Haslam, K; Ioannou, Y; et al.
Objectives: The Systemic Lupus International Collaborating Clinics (SLICC) group proposed revised classification criteria for systemic lupus erythematosus (SLICC-2012 criteria). This study aimed to compare these criteria with the well-established American College of Rheumatology classification criteria (ACR-1997 criteria) in a national cohort of juvenile-onset systemic lupus erythematosus (JSLE) patients and evaluate how patients' classification criteria evolved over time. Methods: Data from patients in the UK JSLE Cohort Study with a senior clinician diagnosis of probable evolving, or definite JSLE, were analyzed. Patients were assessed using both classification criteria within 1 year of diagnosis and at latest follow up (following a minimum 12-month follow-up period). Results: A total of 226 patients were included. The SLICC-2012 was more sensitive than ACR-1997 at diagnosis (92.9% versus 84.1% p < 0.001) and after follow up (100% versus 92.0% p < 0.001). Most patients meeting the SLICC-2012 criteria and not the ACR-1997 met more than one additional criterion on the SLICC-2012. Conclusions: The SLICC-2012 was better able to classify patients with JSLE than the ACR-1997 and did so at an earlier stage in their disease course. SLICC-2012 should be considered for classification of JSLE patients in observational studies and clinical trial eligibility.